Expression of a Secretory Protein C1qTNF6, a C1qTNF Family Member, in Hepatocellular Carcinoma - Tamotsu Takeuchi; Yoshihiro Adachi; Tomoko Nagayama (Analytical Cellular Pathology)
Background: Recent studies have revealed that the adiponectin-associated protein belonging to the C1qTNF family mediates various biological processes. However, the pathobiological property of C1qTNF6 in carcinogenesis remains unclear. Here, we investigated the expression status of C1qTNF6 in human hepatocellular carcinomas and subsequently attempted to determine the role of C1qTNF6 in tumor neovascularization. Methods: Immunohistochemical staining was performed to evaluate the expression of C1qTNF6 in hepatocellular carcinoma tissue specimens. Various eukaryotic recombinant C1qTNF6 proteins were prepared to ask whether C1qTNF6 could activate Akt pathway in human liver sinusoidal microvascular endothelial cells. Xenograft assay was carried out to know the effect of C1qTNF6 on tumor neovascularization. Results: C1qTNF6 was not immunohistochemically detected in any non-cancerous liver tissues but was detected in 21 of 30 hepatocellular carcinoma tissue specimens. C1qTNF6 was not uniformly distributed but rather focally localized in hepatocellular carcinoma cells. Interestingly, it was also localized on the tumor endothelial cells, which were in close proximity of C1qTNF6-expressing hepatocellular carcinoma cells. Eukaryotic recombinant C1qTNF6 increased the level of active phosphorylated Akt molecules in cultured vascular endothelial cells via its C-terminal C1q domain. In the xenograft assay, enforced expression of C1qTNF6 markedly reduced the central hypovascular necrosis areas of the transplanted HepG2 hepatocellular carcinoma cells. Conclusion: These results indicate that C1qTNF6 is overexpressed and possibly contributes to tumor angiogenesis by activating the Akt pathway in many hepatocellular carcinomas.